Assessing collaboration among team scientists within a triadic research center partnership - Linda S. Behar-Horenstein; Joyce R. Richey; Ukamaka Diké Smith (Qualitative Research in Medicine & Healthcare)
Few studies have utilized qualitative methods to assess the perceived effectiveness of collaboration among research center interdisciplinary team scientists. Stages of team development served as the theoretical framework to characterize minority serving institution (MSI) and predominantly White institutions (PWI) participants’ challenges and successes during a National Institutes of Health (NIH) sponsored cancer health disparities training and research program. We present the finding of an inductive analysis of four open-ended survey questions across two years. Fostering an awareness of the inherently taxing, yet centrality of group (team) development may advance an understanding of team dynamics and lead to increased team cohesion and productivity. In conclusion, we provide recommendations to assist multiple principal investigators who embark on team development.